Ethics of artificial intelligence - Liao, S. Matthew (New York, NY, United States of America : Oxford University Publication, 2020)
"Featuring seventeen original essays on the ethics of Artificial Intelligence (AI) by some of the most prominent AI scientists and academic philosophers today, this volume represents the state-of-the-art thinking in this fast-growing field and highlights some of the central themes in AI and morality such as how to build ethics into AI, how to address mass unemployment as a result of automation, how to avoiding designing AI systems that perpetuate existing biases, and how to determine whether an AI is conscious. As AI technologies progress, questions about the ethics of AI, in both the near-future and the long-term, become more pressing than ever. Should a self-driving car prioritize the lives of the passengers over the lives of pedestrians? Should we as a society develop autonomous weapon systems that are capable of identifying and attacking a target without human intervention? What happens when AIs become smarter and more capable than us? Could they have greater than human moral status? Can we prevent superintelligent AIs from harming us or causing our extinction? At a critical time in this fast-moving debate, thirty leading academics and researchers at the forefront of AI technology development come together to explore these existential questions, including Aaron James (UC Irvine), Allan Dafoe (Oxford), Andrea Loreggia (Padova), Andrew Critch (UC Berkeley), Azim Shariff (Univ. of British Columbia), Carrick Flynn (Oxford), Cathy O'Neil (O'Neil Risk Consulting & Algorithmic Auditing), Eliezer Yudkowsky (Machine Intelligence Research Institute), Eric Schwitzgebel (UC Riverside), Frances Kamm (Rutgers), Francesca Rossi (IBM), Hanna Gunn (UC Merced), Iyad Rahwan (MIT), Jessica Taylor (Median Group), JF Bonnefon (Centre National de la Recherche Scientifique), K. Brent Venable (Tulane), Kate Devlin (King's College London), Mara Garza (UC Riverside), Nicholas Mattei (Tulane), Nick Bostrom (Oxford), Patrick LaVictoire (Lyft), Peter Asaro (The New School), Peter Railton (Michigan), S. Matthew Liao (NYU), Shannon Vallor (Santa Clara), Stephen Wolfram (Wolfram Research), Steve Petersen (Niagara), Stuart Russell (UC Berkeley), Susan Schneider (Univ. of Connecticut), Wendell Wallach (Yale)"--
Includes bibliographical references and index.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: Artificial intelligence -- Moral and ethical aspects